ISU-ISU KONTEMPORER MANAJEMEN PENDIDIKAN ISLAM - Hasan Khariri (ADIBA : JOURNAL OF EDUCATION, 2024)
This research aims first, to determine the objectives of Islamic education management. Second, to understand the management process of Islamic education in institutions, especially Islamic institutions. Third, to find out contemporary issues in Islamic education management today. This research uses a literature review method. The steps for this research are to collect literature sources that support the research, read and analyze the literature, then process the research material into a literature study. The results of this research are first, the aim of Islamic education management is to realize an effective and efficient educational process in achieving the goals of Islamic education. In general, the objectives of Islamic education management can be categorized into two, namely: 1) forming human beings, and 2) preparing generations of Muslims. Second, the Islamic education management process includes: 1) planning, 2) organization, 3) leadership, 4) control, 5) Islamic principles, namely: the principle of monotheism, the caliphate principle, the principle of ta'awun, and the principle of ihsan. Third, contemporary issues in Islamic education management include: 1) challenges of globalization, 2) quality of teaching staff or human resources, 3) changes in curriculum, 4) learning methods that have not been innovated, 5) inadequate facilities and infrastructure, 6) financial management which is not yet transparent, 7) Lack of cooperation with other parties, and 8) funding.